Characterization of an envelope gene VP19 from Singapore grouper iridovirus - Huang, Xiaohong (BioMed Central, 2013)
BACKGROUND: Viral envelope proteins are always proposed to exert important function during virus infection and replication. Vertebrate iridoviruses are enveloped large DNA virus, which can cause great economic losses in aquaculture and ecological destruction. Although numerous iridovirus envelope proteins have been identified using bioinformatics and proteomic methods, their roles in virus infection remained largely unknown. METHODS: Using SMART and TMHMM programs, we investigated the structural characteristics of Singapore grouper iridovirus (SGIV) VP19. A specific antibody against VP19 was generated and the expression profile of VP19 was clarified. The subcellular localization of VP19 in the absence or presence of other viral products was determined via transfection and immune fluorescence assay. In addition, Western blot assay and electron microscopy examination were performed to demonstrate whether SGIV VP19 was an envelope protein or a capsid protein. RESULTS: Here, SGIV VP19 was cloned and characterized. Among all sequenced iridoviruses, VP19 and its orthologues shared common features, including 19 invariant cysteines, a proline-rich motif and a predicted transmembrane domain. Subsequently, the protein synthesis of VP19 was only detected at the late stage of SGIV infection and inhibited obviously by treating with AraC, confirming that VP19 was a late expressed protein. Ectopic expression of EGFP-VP19 in vitro displayed a punctate pattern in the cytoplasm. In SGIV infected cells, the newly synthesized VP19 protein was initially localized in the cytoplasm in a punctate pattern, and then aggregated into the virus assembly site at the late stage of SGIV infection, suggesting that other viral protein products were essential for VP19’s function during SGIV infection. In addition, Western blot assay and electron microscopy observation revealed that SGIV VP19 was associated with viral envelope, which was different from major capsid protein (MCP). CONCLUSION: Taken together, the current data suggested that VP19 represented a conserved envelope protein in iridovirus, and might contribute greatly to virus assembly during virus infection.